(untitled) (UNIZIK Journal of Educational Management and Policy, 2026)
The study examined teacher’s use of appropriate teaching methods and effective communication skills as classroom management practices for promoting student’s academic engagement in Anambra State. Two research questions guided the study while two hypotheses were tested at 0.05 alpha level. A descriptive survey research design was adopted for the study. The population of the study comprised of 1072 male and 6176 female teachers making 7,248 in the 267 schools in the six education zones of Anambra State. A sample size of 487 made up of 64 male and 423 female teachers in government owned secondary schools in the selected Education Zones was drawn using multistage sampling procedure. A researcher-developed questionnaire title Teachers’ Classroom Management Practices for Promoting Students’ Academic Engagement in Secondary School (TCMPPSAESS) was used for data collection. The instrument was validated by three experts. The reliability of the instruments was established using Cronbach alpha method. The reliability of instrument coefficients obtained was an overall index of 0.986. In answering the research questions and testing the hypotheses, descriptive (mean and standard deviation) and inferential (t-test) statistics were used. The findings revealed among others that teachers’ use of appropriate teaching methods, and effective use of communication skills promote students’ academic engagement. The study concluded that both female and male teachers’ use of appropriate teaching methods, and effective use of communication skills as classroom management practices promote students’ academic engagement in Anambra State and thus recommended among others that curriculum planners should propose more effective strategies that would continue to enhance teachers’ classroom management practices for better engagement of students academically in Anambra State.